MOSQUE MANAGEMENT ACTIVITIES IN REALIZING THE "RAMAH MUSAFIR" CONCEPT AS A FORM OF SERVICE TO THE COMMUNITY AT ARRIDHO MOSQUE, PERUMNAS MANDALA, MEDAN DENAI DISTRICT - Tarmizi Harahap; Kamalia (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the implementation of the planning function in the management of Arridho Perumnas Mandala Mosque, with the goal of realizing a traveler-friendly concept as a form of service to the community. The research is motivated by the gap between the ideal conditions (Das Sollen) for managing a traveler-friendly mosque and the actual conditions (Das Sein) in the field; while the needs of congregants and travelers regarding mosque facilities continue to rise, these have not yet been fully matched by structured service planning. A qualitative approach involving field research was employed. Data were collected using three techniques: observation, interviews, and document analysis. The findings indicate that the planning undertaken by the mosque administrators encompassing the development of service programs, physical facilities, digital technology utilization, and community engagement serves as a determining factor in establishing a traveler-friendly mosque. The study concludes that structured planning enhances the quality of service to the community and strengthens the mosque's role as a center of Islamic civilization.